Hubungan Bullying dengan Kesehatan Mental kepada Siswa SMA Negeri 6 Kota Kupang - Papy Jose Loban; R. Pasifikus Ch. Wijaya; M.K.P Abdi Keraf (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
Bullying remains a significant issue within educational environments due to its potential impact on students' psychological well-being and mental health. This study aimed to examine the effect of Bullying on the mental health of students at SMA Negeri 6 Kupang City. A quantitative approach with a cross-sectional design was employed. The study involved 88 students selected using a convenience sampling technique from a population of 1,094 students. Data were collected using the Olweus Bully/Victim Questionnaire (OBVQ) to measure Bullying and the Mental Health Inventory-18 (MHI-18) to assess mental health. Data analysis was conducted using descriptive statistics and simple linear regression. The results indicated that the average Bullying score was 30.76, while the average mental health score was 55.20. Regression analysis revealed a negative relationship between Bullying and mental health (β = -0.200), indicating that higher levels of Bullying tended to be associated with lower mental health scores. However, the relationship was not statistically significant (p = 0.062 > 0.05). The coefficient of determination (R² = 0.040) showed that Bullying explained only 4% of the variance in students’ mental health. These findings suggest that although Bullying tends to negatively affect mental health, other factors play a more substantial role in determining adolescents' mental health conditions.